Effects of 2D&3D nonparallel flaws on failure characteristics of brittle rock-like samples under uniaxial compression: Insights from acoustic emission and DIC monitoring. (August 2022) - Zhao, Yusong; Chen, Congcong; Wu, Shunchuan; Guo, Pei; Li, Binglei
Highlights: The 2D through-type and 3D internal-type nonparallel flaw represents the visible and concealed fracture structure, respectively; AE events densely gather around the internal 3D flaw, accompanied by evident acoustic, optical and mechanical responses; Occurrence of b-value sharp change is commonly no later than the AE burst, which is possible to be an important precursory information for the large scale secondary failures in rock. Occurrence of internal macro cracks is earlier than the surface secondary cracks, and it is hard to discover the spatial correlation between them. Abstract: The occurrence of preset flaws can influence the mechanical, physical and other related properties of rock samples. To study the failure characteristics of rock samples with 2D&3D nonparallel flaws, the Digital Image Correlation and Acoustic Emission technologies are employed in the uniaxial compression test. Test results indicate: 1) Acoustic emission events densely gather around the internal 3D flaw, accompanied by acoustic (Acoustic emission rate, amplitude and cumulative counts), optical (strain field) and mechanical (stress fluctuation) responses; 2) The secondary failures mainly reflect in two ranges of AE signal frequency (distributes in 100–160 kHz and 270–330 kHz, and reach peak amplitude at 130 kHz and 310 kHz), and the proportion of low-frequency events decreases as the flaw inclination increases; 3) Occurrence of b -value sharp change is commonly no later than the AE burst, and the sudden fall of b -value is possible to be an important precursory information for the large scale secondary failures in rock; 4) The appearance time of internal macro cracks is earlier than the surface secondary cracks when the sample contains both 2D and 3D flaws, and it is difficult to build the spatial correlation between them.